2007
DOI: 10.1001/archinte.167.9.879
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Serum Phosphorus and Calcium Levels to the Incidence of Cardiovascular Disease in the Community

Abstract: Background: Higher levels of serum phosphorus and the calcium-phosphorus product are associated with increased mortality from cardiovascular disease (CVD) in patients with chronic kidney disease (CKD) or prior CVD. However, it is unknown if serum phosphorus levels influence vascular risk in individuals without CKD or CVD. Methods:We prospectively evaluated 3368 Framingham Offspring study participants (mean age, 44 years; 51% were women) free of CVD and CKD. We used multivariable Cox models to relate serum phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
542
5
21

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 765 publications
(595 citation statements)
references
References 45 publications
27
542
5
21
Order By: Relevance
“…The positive phosphate balance seems to cause an accelerated progression of vascular calcification. [5][6][7][8] An acute phosphate load that overwhelms renal capacity for excretion can be derived from endogenous and exogenous sources. Large amounts of endogenous phosphates are released from intracellular stores in tumor lysis syndrome, rhabdomyolysis, and lactic acidosis.…”
mentioning
confidence: 99%
“…The positive phosphate balance seems to cause an accelerated progression of vascular calcification. [5][6][7][8] An acute phosphate load that overwhelms renal capacity for excretion can be derived from endogenous and exogenous sources. Large amounts of endogenous phosphates are released from intracellular stores in tumor lysis syndrome, rhabdomyolysis, and lactic acidosis.…”
mentioning
confidence: 99%
“…A associação entre Pi e morbimortalidade foi demonstrada há alguns anos, inicialmente na população de portadores de DRC em hemodiálise no clássico estudo de Block e cols. 8 , e, posteriormente, confirmada em diversas outras coortes tanto em indivíduos com DRC quanto naqueles com função renal preservada [9][10][11][12] . Análise dos dados de pacientes originários de 12 países participantes do DOPPS (Dialysis Outcomes and Practice Pattern Study) mostrou que níveis séricos de Pi entre 6,1 e 7,0 mg/dL e acima de 7,1 mg/dL no início do estudo conferiam um aumento no risco de morte por qualquer causa de 18% e 43%, respectivamente, quando comparados a níveis de Pi na faixa de referência (entre 3,6-5,0 mg/dL).…”
Section: Homeostase Do Fosfatounclassified
“…Uma análise derivada da coorte de Framingham, incluindo mais de 3000 pacientes livres de doenças cardiovasculares e função renal preservada, com tempo médio de seguimento de 16 anos, demonstrou a associação entre Pi sérico basal >3,5 mg/dL e aumento de 55% no risco de eventos cardiovasculares. 11 No estudo Atherosclerosis Risk in Communities (ARIC) (n=15.732), o risco relativo de morte ajustado após análise multivariada foi aumentado em 14% na presença de níveis mais elevados de Pi. 12 Estes dois últimos estudos chamam a atenção pelo fato de que os níveis séricos de Pi onde foi observada maior mortalidade encontram-se ainda dentro da faixa da normalidade, abrindo duas possibilidades: este é um achado apenas de associação, sem nenhuma relação causal específica, onde o Pi é apenas um marcador de risco; ou a faixa de referência por nós utilizada é equivocada e, em alguns indivíduos com outros fatores de risco, Pi sérico acima de 3,5 mg/dL pode levar a maior risco de morte.…”
Section: Homeostase Do Fosfatounclassified
See 1 more Smart Citation
“…In the past two decades, the role of P in the body has been emphasized and innumerous studies have shown the association between P and mortality, [3][4][5][6][7][8][9] suggesting that P could be a toxic element in certain circumstances. However, for many years, P has been believed not to be a deleterious factor in patients with CKD, because it remains within the reference range for a long period in the course of that disease.…”
Section: Introductionmentioning
confidence: 99%